Bridging Legal Gaps: Harmonizing the Roles of BPBD, Bakesbangpol, and Bakorwil in Regional Governance - Permadi Setyonagoro; Himawan Estu Bagijo; Slamet Hari Sutanto; Yudiyanto Tri Kurniawan; Sonya Claudia Siwu (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Good regulations are harmonious laws. Disharmony of laws and regulations gives rise to complex legal issues, at least problematic in the context of fulfilling the objectives of legal uncertainty. One of the dis harmonizations of existing regulations is the regulation regarding the existence of regional institutions in the form of bodies. By using a normative legal study method, this study found that there is a disharmonious form of regulatory material regarding the duties and functions of several regional apparatuses in the form of bodies in Indonesia. There are three regional apparatuses in the form of bodies that have different duties and functions as regulated in Law Number 23 of 2014 concerning Regional Government and Government Regulation Number 18 of 2016 concerning Regional Apparatus, namely Regional Disaster Management Agency (BPPD), the National and Political Unity Agency (Bakesbangpol), and the East Java Province Regional Government and Development Coordinating Agency (Bakorwil). Findings of disharmony in regulatory matters like this have caused several regional government regulations in Indonesia to lack legal certainty. For this reason, it is important to immediately carry out efforts to harmonize the laws and regulations that regulate the duties and functions of regional apparatus in the form of bodies.